Serum albumin and cardiovascular disease: a Mendelian randomization study - Taoke Huang; Zhifeng An; Ziru Huang; Weiyang Gao; Benchuan Hao; Juan Xu (BMC Cardiovascular Disorders, 2024)
Abstract Background An increasing body of evidence suggests that serum albumin levels play a role in cardiovascular diseases. However, the specific causal relationship between serum albumin levels and cardiovascular disease remains partially unknown. Methods Mendelian randomization (MR) was employed in this study to examine potential causal relationships between instrumental variables and cardiovascular diseases. Specifically, we utilized genetic variants of serum albumin levels within the reference range as our instrumental variables. To acquire data on genetic associations with cardiovascular diseases, we sourced information from renowned genome-wide association studies such as UK BioBank, EMBL-EBI, and FinnGen. Notably, our study leveraged summary statistics from large cohorts that have been previously described. Results We explored the association between serum albumin levels and various conditions, including heart failure (HF), venous thromboembolism (VTE), stroke, atrial fibrillation (AF), coronary artery disease (CAD), type 2 diabetes (T2DM), and pulmonary heart disease (PHD). Genetically predicted serum albumin levels were associated with PHD (odds ratio = 0.737, 95% CI = 0.622 − 0.874, P < 0.001), AF (odds ratio = 0.922, 95% CI = 0.870 − 0.977, P = 0.006), VTE (odds ratio = 0.993, 95% CI = 0.991 − 0.995, P < 0.001), and Stroke (odds ratio = 0.997, 95% CI = 0.995 − 0.999, P = 0.002). However, genetically predicted serum albumin level traits were not associated with HF, CAD and T2DM. Conclusion Our study demonstrates a significant association between serum albumin levels and cardiovascular disease, underscoring the crucial role of low serum albumin as a predictive factor in patients with cardiovascular disease.